2014
DOI: 10.1111/asj.12279
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Carotino oil on in vitro rumen fermentation, metabolism and apparent biohydrogenation of fatty acids

Abstract: The study appraised the effects of Carotino oil on in vitro rumen fermentation, gas production, metabolism and apparent biohydrogenation of oleic, linoleic and linolenic acids. Carotino oil was added to a basal diet (50% concentrate and 50% oil palm frond) at the rate of 0, 2, 4, 6 and 8% dry matter of the diet. Rumen inoculum was obtained from three fistulated Boer bucks and incubated with 200 mg of each treatment for 24 h at 39°C. Gas production, fermentation kinetics, in vitro organic matter digestibility (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…This observation lends credence to the result of a companion in vitro study (Adeyemi et al . ) which showed that the apparent biohydrogenation of C18:1n‐9 increased as the level of BCPO increased in the substrate. In addition, the ruminal concentration of C18:2n‐6 and C18:1n‐9 tended to decrease with an increase in dietary BCPO (Adeyemi et al .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…This observation lends credence to the result of a companion in vitro study (Adeyemi et al . ) which showed that the apparent biohydrogenation of C18:1n‐9 increased as the level of BCPO increased in the substrate. In addition, the ruminal concentration of C18:2n‐6 and C18:1n‐9 tended to decrease with an increase in dietary BCPO (Adeyemi et al .…”
Section: Discussionmentioning
confidence: 92%
“…The fatty acid composition and the antioxidant contents of palm oil (Edem 2002) and canola oil (Ghazani et al 2014) have been documented. Previous companion studies have shown that the blend of 80% canola oil and 20% palm oil did not have deleterious effects on the in vitro (Adeyemi et al 2015a) and in vivo (Adeyemi et al 2015c) rumen fermentation, feed intake and growth performance in goats (Adeyemi et al 2015c). Thus, we propose that a blend of 20% palm oil and 80% canola oil will enhance the beneficial fatty acids in goat meat and prevent oxidative spoilage.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, similar in vivo studies are seldom reported for goats. Erstwhile companion in vitro study showed that the blend of 20% palm oil and 80% canola oil had no effect in vitro organic matter (OM) and dry matter (DM) digestibility (Adeyemi et al 2015).…”
Section: Introductionmentioning
confidence: 99%